Beyond genes and environment: mapping biological stochasticity in aging - Adam J. Hruby; Gilberto Garcia; Max A. Thorwald; Caleb E. Finch; Joshua Johnson; Ryo Higuchi-Sanabria (GeroScience, 2025)
Aging is characterized by extensive variability in the onset of morbidity and mortality, even in genetically identical populations with carefully controlled environments. This points to the important role stochasticity plays in shaping the divergent aging process between individual organisms. Here, we survey how stochastic factors at the level of molecules, cells, tissues, and organisms manifest in and impact the aging process, with a focus on the nematode Caenorhabditis elegans . Findings of stochasticity in C. elegans give additional insights for aspects of aging in the more complex settings of mammals with parallels drawn between organisms when appropriate. The emerging understanding of the stochastic contributors to longevity will enhance research strategies and medical interventions for personalized medicine.

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Determining the feasibility of characterising cellular senescence in human skeletal muscle and exploring associations with muscle morphology and physical function at different ages: findings from the MASS_Lifecourse Study - Leena Habiballa; Adam Hruby; Antoneta Granic; Richard M. Dodds; Susan J. Hillman; Diana Jurk; João F. Passos; Avan A. Sayer (GeroScience, 2023)
Cellular senescence may be associated with morphological changes in skeletal muscle and changes in physical function with age although there have been few human studies. We aimed to determine the feasibility of characterising cellular senescence in skeletal muscle and explored sex-specific associations between markers of cellular senescence, muscle morphology, and physical function in participants from the MASS_Lifecourse Study. Senescence markers ( p16 , TAF (Telomere-Associated DNA Damage Foci), HMGB1 (High Mobility Group Box 1), and Lamin B1) and morphological characteristics (fibre size, number, fibrosis, and centrally nucleated fibres) were assessed in muscle biopsies from 40 men and women (age range 47–84) using spatially-resolved methods (immunohistochemistry, immunofluorescence, and RNA and fluorescence in situ hybridisation). The associations between senescence, morphology, and physical function (muscle strength, mass, and physical performance) at different ages were explored. We found that most senescence markers and morphological characteristics were weakly associated with age in men but more strongly, although non-significantly, associated with age in women. Associations between senescence markers, morphology, and physical function were also stronger in women for HMGB1 and grip strength ( r = 0.52); TAF, BMI, and muscle mass ( r > 0.4); Lamin B1 and fibrosis ( r = − 0.5); fibre size and muscle mass ( r ≥ 0.4); and gait speed ( r = − 0.5). However, these associations were non-significant. In conclusion, we have demonstrated that it is feasible to characterise cellular senescence in human skeletal muscle and to explore associations with morphology and physical function in women and men of different ages. The findings require replication in larger studies.